Changes in muscle contractile function and voluntary activation after maximal high-load and moderate-load hexagonal-barbell deadlift exercise - Collison, J. A.; Moran, J. (Journal of Australian Strength and Conditioning, 2020)
This study examined differences in magnitude and recovery of muscle contractile function and voluntary activation after exhaustive high-load and moderate-load hexagonal-barbell deadlift (HBD) exercise. Eight resistance trained males (HBD 3RM 181 ± 26.4 kg; age 27.4 ± 5.7 years, body mass 77.4 ± 11.3 kg) completed two exhaustive resistance exercise protocols using a randomised cross-over design. The protocols performed until volitional exhaustion included: high-load, low repetitions (HLLR) consisting of sets of 3 repetitions at 90% 3RM and moderate-load high repetitions (MLHR) consisting of sets of 10 repetitions at 75% 3RM. Exercise induced changes in maximal voluntary contraction (MVC), voluntary activation (VA), and evoked potentiated twitch torque (Pt) of the knee extensors were determined using the interpolated twitch technique pre-, post-, and 24-h after exercise. Total concentric work, volume load, mean power output, mean barbell velocity, and post-exercise blood lactate concentrations were higher for MLHR. MVC torque (-15.4 ± 10.7%), Pt (-18 ± 14.4%), and VA (-13.1 ± 14.35%) were reduced post MLHR, but not HLLR. Reduced MVC (-12.8 ± 7.7%) was present 24-h after MLHR exercise, which was associated with lowered VA and near recovery of contractile function. In summary moderate-load HBD exercise performed until failure resulted in losses of contractile function and voluntary activation, while MVC was largely preserved after HLLR exercise. The fact that performance fatigability was lowered after HLLR has important implications for strength coaches. For example, during periods of schedule congestion during a sport`s in-season, high-load HBD exercise could be undertaken to minimise longer-term residual fatigue.